A legszelídebb patak: A lutheránus németség tanítókönyvtárai a kora újkori Felvidéken - Mizera, Tamás (Per Aspera ad Astra, 2018)
Our knowledge of the book culture of the citizens of the Carpathian Basin in the Early Modern Period is the outcome of decades of research conducted by generations of scholars. With the help of inventories, which are regarded as the most important sources, we can develop a nuanced picture of primarily the literacy of Lutheran Germans, and the same is true for the libraries of school teachers. Partly thanks to the more and more widespread approaches in the history of education based on reception history, the discipline became open to integrating the results of book-, library- and literacy history, and as a result, the libraries of school teachers which are interpreted as a type of civic libraries are in the center of attention for experts who work on the borderline of the two disciplines. The 21 collections from Upper Hungary belonging to this group mean the highest level of book culture of school teachers in the Carpathian Basin between the 16th and the 18th centuries, both in terms of criteria of quantity and content. The presence of books of theology, daily religious practicies, the literature of pedagogy and linguistics as well as books by classic authors point out an emphatic process. The books, arriving to the area of historical Hungary mostly from the German book market, brought the Western European intellectual trends with themselves including the spread of the early modern programs of pedagogy and education. We can reconstruct the phenomenon with the help of databases at our disposal containing the bibliographical data of old books. The present paper analyzes the collecions of Lutheran, German speaking school teachers of Upper Hungary taking into account the considerations above. Photo: pexels.com